Did life insurers benefit from TARP or regulatory forbearance during the financial crisis of 2008-2009? - Michelle L. Barnes (Federal Reserve Bank of Boston, 2016)
Life insurers' odds of being placed under regulatory control (for example, conservatorship or receivership) during the financial crisis years of 2008 and 2009 increased with deteriorating fundamentals at a much higher rate than during normal times or during the previous recession. However, no life insurer in the sample belonging to a life insurance holding company system (LIHCS) in receipt of TARP funds experienced such insolvency issues, and life insurers with poor and deteriorating performance that belonged to a LIHCS in receipt of TARP funds received increased capital inflows during the crisis years. In contrast, life insurance entities with poor and deteriorating performance but with no access to TARP funds received a smaller dollar amount of capital injections on average during the crisis. Evidence is presented of state-based regulatory forbearance due to prescribed and permitted accounting practices (P&P) during the crisis, and it is shown that such forms of state-based regulatory forbearance acted as a substitute for the receipt of TARP funds.
Keywords: G01; G21; G22; G28; G32; G33; 330; financial crises; financial institutions; life insurers; government policy and regulation; capital and ownership structure; solvency